If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y+2-3=0
We add all the numbers together, and all the variables
y-1=0
We move all terms containing y to the left, all other terms to the right
y=1
| 6h+h+11h=90+18 | | X+8=x^2+3x-7 | | 2x+3(x-2)=30,x= | | 8y+(-2)=8y+(-2) | | -x-4=2x+11 | | 2k-3=4k-2 | | (X-3)(x-3)-64=0 | | 5x+38=2x-10 | | (7x+9)−(5+3x)=36 | | 2x–6=2x+ | | m-25=246 | | p=p/100 | | 1/3(x-30)=65 | | –9v−2=–10−8v | | 10–2y=16 | | 16/b=56/38.4 | | 0,05x-0.08+x=0.97 | | a/7+9=4 | | 4x^-6x+58=0 | | 22+3c=43 | | 6x−(2+3x)=22 | | 5x=36-4x. | | x-45=117 | | m/5+6=18 | | 1=k/9 | | 6b–12=12 | | 5q-42=59 | | 2x+1=-31.4 | | 3g=33 | | 25=40-y | | 8(3x-9)=6x+18 | | 9^2x+3=27^x+2 |